Exploring the Use of Pegylated Liposomal Doxorubicin (Caelyx®) as Pressurized Intraperitoneal Aerosol Chemotherapy - Robella, Manuela; Vaira, Marco; Argenziano, Monica; Spagnolo, Rita; Cavalli, Roberta; Borsano, Alice; Gentilli, Sergio; De Simone, Michele (Frontiers in Pharmacology, 2019)
Background: Peritoneal carcinomatosis is a common metastatic pattern in ovarian, gastric, colorectal and appendiceal cancer; systemic chemotherapy is the current standard of care for peritoneal metastatic disease; however, in a subset of patients its beneficial effect remains questionable. More effective perioperative chemotherapy is needed. Materials and Methods: PIPAC is a new treatment that applies chemotherapeutic drugs into the peritoneal cavity as an aerosol under pressure. It's a safe and feasible approach that improves local bioavailability of chemotherapeutic drugs as compared with conventional intraperitoneal chemotherapy. Till now the drugs used in PIPAC are Cisplatin, Doxorubicin and Oxaliplatin; as of yet, there are no in vivo data comparing different drug formulations and dosage schedules of PIPAC. Pegylated Liposomal Doxorubicin 1,5 mg/sm was aerosolized. Results: pharmacokinetics analysis of 10 procedures performed with conventional Doxorubicin solution at the dose of 1.5 mg/m2 were compared to 15 procedures with the same dose of PLD. Significant differences between experimental groups were detected by one-way ANOVA followed by Bonferroni correction; a p value < 0.05 was considered statistically significant. A statistically different doxorubicin tissue concentration was observed for the doxorubicin solution compared to pegylated liposomal doxorubicin in the right parietal and diaphragmatic peritoneum. In the Caelyx® series a mean tissue concentration of 1.27 ± 1.33 mg/g was reported, while in the second one we registered a mean concentration of 3.1 ± 3.7 mg/g. Conclusions: The delivery of nano-particles in PIPAC was feasible, but PLD concentrations are lower than standard doxorubicin.